Simplify. Express using exponents.
2n^{2}(8)^{3} ==> 2n^{2} · 8^{3}
8^{3} = 8 · 8 · 8 = 512
2n^{2} · 8^{3} = 2n^{2} · 512 = (512 · 2)n^{2} = 1024n^{2 }
Simplify. Express using exponents.
2n^{2}(8)^{3} ==> 2n^{2} · 8^{3}
8^{3} = 8 · 8 · 8 = 512
2n^{2} · 8^{3} = 2n^{2} · 512 = (512 · 2)n^{2} = 1024n^{2 }
With instructions to use exponents, I would do it this way:
2n^{2}(8)^{3 } = 2(2^{3})^{3} n^{2} = 2(2^{9}) n^{2} = 2^{10} n^{2}
This is exactly the same as Tamara's answer above, but with an explicit powr of 2.